Pluralist publics in market driven education : towards more democracy in educational reform - Boyask, Ruth (London [England] : Bloomsbury Academic, 2020)
"Pluralist Publics in Market Driven Education opens a conversation on the nature of the public in education systems weary from market driven educational reform. Ruth Boyask observes the characteristic of publicness within contemporary education settings, a characteristic defined by tools from public sphere and democratic education theory. Boyask's investigations of publicness in educational sites are founded in conceptualising public education as pluralist, unbounded and conditional. These concepts of the public are important for ongoing and future debate on public education. The settings Boyask examines are different in structure, function and location yet each demonstrates the push and pull between market relations (including competition, efficiency and productivity) and the desire for social equality and democracy in education. Examples of educational settings are drawn broadly from an Anglo-American imaginary that has taken hold in educational systems transnationally, with detailed observation from three research studies of education policy enactment in England. The research studies (including research on curriculum reform in a private democratic school, privatisation of regional educational services and governance in English private schools) provide contexts for examining public accountability, public service and the public good as they relate to a reconceptualised public education. Boyask's argument is that by opening a conversation about the nature of the public within these sites we bring them into the spheres of a pluralist public education. They become open to public scrutiny and through their debate arise new ideas for challenging market-driven restrictions to contemporary public education. Ruth Boyask is Senior Lecturer at Auckland University of Technology, New Zealand, where she does research and teaches on postgraduate programmes in education. Previously, she was Lecturer in Education Studies at the University of Plymouth, UK, and remains a member of Council for the British Educational Research Association."--
1. Visualising Pluralist Public Education -- 2. Theorising Pluralist Public Education -- 3. Opening a Window on the Private Sphere -- 4. Mapping Governance Structures -- 5. Public Accountability -- 6. Public Service -- 7. Public Benefit/Public Good -- 8. Public Education Unbounded -- References -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Privatization in education; Educational accountability; Educational strategies & policy; Electronic books